PENYALAHGUNAAN FUNGSI TROTOAR DARI PERSPEKTIF PERATURAN DAERAH NOMOR 1 TAHUN 2018 TENTANG KETERTIBAN UMUM DI KOTA GORONTALO - Ridho Akbar Utiarahman; Zamroni Abdussamad; Nuvazria Achi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
Sidewalks are public facilities provided to ensure the safety and comfort of pedestrians and to support traffic order in urban areas. However This study aims to analyze the misuse of sidewalks in light of Gorontalo City Regulation No. 1 of 2018 on Public Order and to formulate policy recommendations for the management and utilization of sidewalks without compromising their primary function for pedestrians. The research method employed is normative legal research using a legislative approach and a conceptual approach. The legal materials used include primary, secondary, and tertiary sources, analyzed using a descriptive-qualitative approach. The results indicate that the misuse of sidewalks in Gorontalo City persists due to inconsistent law enforcement, limited local government authority over provincial roads, low public legal awareness, and economic factors affecting street vendors.